Studi tentang kasus bullying di Sekolah Dasar Negeri 1 Kayumas Kabupaten Klaten - Retnaningsih, Rahayu; Praheto, Biya Ebi; Megawati, Ida; Rahayu, Sekti (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
This study aims to: (1) Identify the types of bullying that occur within the environment of SD N 1 Kayumas Klaten; and (2) Describe students’ understanding of the concept of bullying in the school setting. This research employs a qualitative approach using a case study method, focusing on an in-depth exploration of the bullying phenomenon within the context of education. This approach aligns with the research objective, which is not to test a specific hypothesis, but to obtain a comprehensive and realistic picture of students’ conceptual understanding of bullying, its impacts, and the strategies for its prevention. The case study method provides a detailed and holistic explanation of various aspects related to individuals, groups, programs, or social situations. The findings of this research indicate: (1) Bullying at SD N 1 Kayumas primarily manifests in the form of verbal bullying, often carried out spontaneously by students due to peer social influence, and frequently misunderstood as mere teasing or joking; and (2) The dominant form of bullying found at SD N 1 Kayumas Klaten is physical appearance-related ridicule, which leads to psychological distress among students.